60.1.440 problem 442

Internal problem ID [10454]
Book : Differential Gleichungen, E. Kamke, 3rd ed. Chelsea Pub. NY, 1948
Section : Chapter 1, linear first order
Problem number : 442
Date solved : Monday, January 27, 2025 at 07:45:54 PM
CAS classification : [_linear]

\begin{align*} x^{2} {y^{\prime }}^{2}+\left (x^{2} y-2 y x +x^{3}\right ) y^{\prime }+\left (y^{2}-x^{2} y\right ) \left (1-x \right )&=0 \end{align*}

Solution by Maple

Time used: 0.003 (sec). Leaf size: 21

dsolve(x^2*diff(y(x),x)^2+(x^2*y(x)-2*x*y(x)+x^3)*diff(y(x),x)+(y(x)^2-x^2*y(x))*(1-x) = 0,y(x), singsol=all)
 
\begin{align*} y &= \left (-x +c_{1} \right ) x \\ y &= x \,{\mathrm e}^{-x} c_{1} \\ \end{align*}

Solution by Mathematica

Time used: 0.055 (sec). Leaf size: 26

DSolve[(1 - x)*(-(x^2*y[x]) + y[x]^2) + (x^3 - 2*x*y[x] + x^2*y[x])*D[y[x],x] + x^2*D[y[x],x]^2==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to c_1 e^{-x} x \\ y(x)\to x (-x+c_1) \\ \end{align*}